MULTILEVEL LOGISTIC ANALYSIS OF INFANT MORTALITY IN NIGERIA ACROSS THE GEOPOLITICAL ZONES - Anche, Joshua; Chukwuemeka, Lawrence Ani; Abduljalal, Kabiru Hassan (FUDMA Journal of Sciences, 2025)
Nigeria faces high child mortality rates, with an under-five mortality rate of 110 per 1,000 live births and an infant mortality rate of 63 per 1,000 in 2023, down from 64.7 in 2020, yet among the highest globally. Regional disparities persist, with 140 deaths per 1,000 in the North West versus 42 in the South West, driven by socioeconomic inequalities (142 per 1,000 in poorest households vs. 49 in wealthiest, 2022). Key causes include neonatal disorders, respiratory infections, malaria, and diarrhea, linked to limited healthcare access, low maternal education, and rural-urban divides. This study examines individual and group-level factors influencing infant mortality from 2020-2025, focusing on regional variations across Nigeria’s geopolitical zones. Using multilevel logistic regression on 2023-24 Nigeria Demographic and Health Survey data (39,050 women aged 15-49 and children, nested in states), three models were analyzed: an intercept-only model, one with individual factors (child’s sex, birth size, mother’s education and age, postnatal checks, antenatal visits, delivery place, residence), and a full model adding state-level zones. Results show rural residence (OR=1.45), male sex, younger maternal age, low education, low birth weight, and no postnatal checks increase risks. North West and North East zones show significant effects, with state-level variance explaining 9-12% of differences. These findings highlight the interplay of individual and contextual factors, urging policymakers to invest in zone-specific health infrastructure, education, and training under the Nigeria Child Survival Action Plan 2025-2029 to address inequalities and reduce preventable deaths.